Problematic internet use in early adolescence: gender and depression differences in a latent growth curve model - Peng Wang; Xiqing Yuan; Tao Gao; Xiao Wang; Qiulian Xing; Xinyu Cheng; Yu Ming (Humanities & Social Sciences Communications)
Abstract This study examined whether there are gender differences in the developmental trajectory of Problematic Internet Use (PIU) and the impact of developmental changes in depression on PIU development, based on the cognitive-behavioral model and the Psychological Needs Compensation model. The study used the Latent growth curve model to analyze 3-year trace data from Chinese adolescents in grades 6 to 9. The findings revealed that the initial level of PIU during early adolescence was significantly greater than 0, with higher levels in boys compared to girls. A progressive trend in PIU development was observed, which decelerated over time, and no significant gender differences were found. Additionally, a rising pattern was identified in the development of depression. The change rate of depression was a highly significant positive predictor of the change rate in PIU. These findings contribute to an enhanced comprehension of the relationship between depression and the development of adolescent PIU, offering scientific guidance for the promotion of adolescents’ physical and mental well-being.